Theory of African Music Volumes I and II. Gerhard Kubik. 2010. Chicago: University of Chicago Press. Vol I, 464 pp., Vol II, 359 pp. - Carver, Mandy (International Library of African Music, 2011)
pages: 250-251
Keywords: African Music